Neohybos gen. nov. (Diptera, Empidoidea, Hybotinae) from the Neotropical Region - Ale-Rocha, R.; de Carvalho, C. J.b. (Zootaxa, 2003)
The new genus Neohybos (Diptera, Empidoidea, Hybotinae) is described from the Neotropical Region. The following new combinations are listed: Neohybos hallexus (Smith), Neohybos halteralis (Bezzi), Neohybos luridus (Bezzi) and Neohybos derodactylus (Melander). The male terminalia of N. luridus (Bezzi), comb. nov., is described and illustrated. The relationships of Neohybos with other genera of Hybotinae are discussed. Key to Neotropical genera of Hybotinae is provided.